Attributed Contribution of Therapist’s Emotional Variables to Psychotherapeutic Effectiveness: A Preliminary Study - Romero-Moreno, Antonio; Paramio, Alberto; Cruces-Montes, Serafín; Zayas, Antonio; Guil, Rocío (Frontiers in Psychology, 2021)
Background The aim of this manuscript is to analyze the degrees of responsibility for healing that psychotherapists attribute to a set of emotional variables of the therapist involved in the therapeutic process. Such variables, framed within the well-known common factors in psychotherapy, have been proven to be essential in making the therapeutic process effective, as has been shown by research in psychotherapy in recent decades. Materials and Methods Based on an extensive literature review, the responses from a sample of 69 psychotherapists to a tool created ad hoc are analyzed to verify whether their attributions are in line with the results of said review. Results The therapists have doubts about the factors responsible for psychotherapeutic effectiveness, as well as about the value of common variables, including those of an emotional nature, not valuing them above those of a specific type. They also argue against the similar effectiveness of different psychotherapeutic models. Conclusion Discrepancies have thus been found between the conclusions reached by research on therapeutic processes and the statements made by the therapists studied, which could indicate an insufficient impact of psychotherapeutic research on clinical practice. We also propose courses of action such as establishing training programs for the acquisition and development of emotional skills for therapists that could increase the effectiveness of their interventions.